2020
DOI: 10.1186/s12935-020-01565-5
|View full text |Cite
|
Sign up to set email alerts
|

LOXL1-AS1 contributes to the proliferation and migration of laryngocarcinoma cells through miR-589-5p/TRAF6 axis

Abstract: Background LOXL1-AS1 is a long non-coding RNA (lncRNA) that plays crucial roles in various cancers. However, the functional role of LOXL1-AS1 in laryngocarcinoma remains unclear. Thus we planned to probe into the function and underlying mechanism of LOXL1-AS1 in laryngocarcinoma. Methods Gene expression was evaluated in laryngocarcinoma cells using RT-qPCR. The ability of cell proliferation and migration was assessed by CCK8, colony formation, wound healing and transwell assays. The interaction among LOXL1-A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 32 publications
0
15
0
Order By: Relevance
“…Another research demonstrated that lncRNA LOXL1-AS1 affected ovarian cancer cell growth, migratory, and invasion by modulating the miR-18b-5p/VMA21 axis [ 23 ]. It was reported that LOXL1-AS1 had an influence on the proliferation and migration of several other cancers by regulating some key genes [ 24 , 25 ]. In the present study, we observed that the expression level of LOXL1-AS1 in liver cancer tissue was significantly higher than that in adjacent normal tissues and its expression in three hepatic carcinoma cell lines was obviously higher than that in a normal cell line.…”
Section: Discussionmentioning
confidence: 99%
“…Another research demonstrated that lncRNA LOXL1-AS1 affected ovarian cancer cell growth, migratory, and invasion by modulating the miR-18b-5p/VMA21 axis [ 23 ]. It was reported that LOXL1-AS1 had an influence on the proliferation and migration of several other cancers by regulating some key genes [ 24 , 25 ]. In the present study, we observed that the expression level of LOXL1-AS1 in liver cancer tissue was significantly higher than that in adjacent normal tissues and its expression in three hepatic carcinoma cell lines was obviously higher than that in a normal cell line.…”
Section: Discussionmentioning
confidence: 99%
“…LSCC, which is of epithelial origin, is a most common tumor of the upper respiratory tract [23]. Poor living habits, such as imbalanced diet, smoking, and alcohol consumption, are the main risk factors contributing to laryngeal cancer [24].…”
Section: Discussionmentioning
confidence: 99%
“…Then, the cells were rinsed with PBS three times to remove floating cells, and incubated in serum-free DMEM to inhibit cell proliferation and division. At 0 and 24 h after wounding and culture, the migration distance of cells in the wound area was observed under a microscope, and several different fields of view were randomly selected for photographing (He et al, 2020). The experiment was repeated three times.…”
Section: Wound Healing Assaymentioning
confidence: 99%